Highly purified CD25(−) resting T cells cannot be infected de novo with HIV-1 - Chou, Chin-Sheng (The National Academy of Sciences of the USA, 1997)
Previous studies have demonstrated that the expression of CD25 can distinguish CD25(−) latently infected cells from CD25(+) cells actively producing virus. Our studies were designed to characterize the nature and stability of the viral genome in CD25(−) quiescent HIV-1-infected cells and to determine whether these cells could be infected de novo with HIV-1. Our results show that: (i) When unfractionated peripheral blood mononuclear cells are first infected with HIV-1 and the CD25(−) cells then isolated, the latter contain only incomplete DNA transcripts and no full-length DNA or 2-LTR circles. Phytohemagglutinin activation of these CD25(−) cells results in the generation of full-length viral DNA and p24 production. (ii) When CD25(−) CD4(+) cells are first purified from peripheral blood mononuclear cells and then incubated with HIV-1, viral DNA cannot be detected, suggesting that these purified cells cannot be infected. Furthermore, CD25(−) adherent cells do not facilitate the infection of CD4(+) CD25(−) T cells when they were present at the time of incubation with HIV-1. Taken together, these studies suggest either that (i) the CD25(−) cells containing incomplete DNA transcripts are derived from infected-activated CD25(+) cells, which subsequently become CD25(−) or (ii) the presence of CD25(+) cells is required for the infection of CD25(−) cells in vitro.